Aripiprazole salts: I. Aripiprazole nitrate - Freire Espeleta, Eleonora (2012)
The crystal structure of aripiprazole nitrate (systematic name: 4-(2,3-dichloro-phen-yl)-1-{4-[(2-oxo-1,2,3,4-tetra-hydro-quino-lin-7-yl)-oxy] but-yl}piperazin-1-ium nitrate), C 23H 28Cl 2N 3O 2 +·NO 3 - or AripH +·NO 3 -, is presented and the mol-ecule com-pared with the aripiprazole molecules reported so far in the literature. Bond distances and angles appear very similar, except for a slight lengthening of the C - NH distances involving the protonated N atom, and the main differences are to be found in the mol-ecular spatial arrangement (revealed by the sequence of torsion angles) and the inter-molecular inter-actions (resulting from structural elements specific to this structure, viz. the nitrate counter-ions on one hand and the extra protons on the other hand as hydrogen-bond acceptors and donors, respectively). The result is the formation of [100] strips, laterally linked by weak π-π and C - Cl⋯π inter-actions, leading to a family of undulating sheets parallel to (010).